Enhancing tribological and corrosion characteristics of AA2099/GNP metal matrix nanocomposites through parametric optimization using Taguchi Technique - Ch Polayya; C S P Rao; Veeresh Kumar G B (Materials Research Express)
The synergy between AA2099 alloys and Graphene Nanoparticles (GNP) harnesses the potential of ultrasonic-assisted stir casting to create metal matrix composites (MMCs). The GNP content is systematically varied (0%, 0.1%, 0.2%, and 0.3%) within the AA2099 alloy matrix. The microstructural analysis employs scanning electron microscopy (SEM) and x-ray diffraction (XRD), while hardness is evaluated using specialized Vickers microhardness equipment. The results reveal a significant improvement in hardness with increasing GNP reinforcement content. Wear behavior investigations utilize pin-on-disc wear tests, guided by the Taguchi Technique and analyzed through an L16 array. Additionally, the influence of various factors on the wear rate and coefficient of friction (COF) is systematically analyzed using Analysis of Variance (ANOVA), highlighting the significant role of GNP content in both wear behavior and COF in these MMCs. SEM analysis of wear fractography provides insights into the fracture behavior of the specimens, elucidating wear mechanisms at the microscale. Lastly, corrosion testing demonstrated that higher GNP content enhances corrosion resistance, as indicated by lower corrosion current density and less negative corrosion potential. Optical microscopy (OM) confirmed that increased GNP content reduces corrosion pit size and enhances protective layer formation.